2021
DOI: 10.1016/j.radonc.2021.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and dosimetric evaluation of carbon ion radiation-induced osteoradionecrosis of mandible in head and neck tumors

Abstract: Background and purpose: Osteoradionecrosis (ORN) affects the patient's quality of life by making eating and maintaining oral hygiene painful. This study aimed to analyze carbon ion radiotherapy (C-ion RT)induced ORN of the mandible. Materials and methods: A retrospective study of 199 patients with head and neck tumors treated with Cion RT was performed from 2010 to 2019. Only 11 patients with tumors located in the oropharynx and floor of the mouth were analyzed. C-ion RT consisted of 57.6 Gy or 64.0 Gy (relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 26 publications
0
20
0
3
Order By: Relevance
“…These data, together with data with conventional photon RT on the impact of dental infection on ORN incidence ( 28 ), confirm the benefit of pre-CIRT prophylactic dental avulsion and oral hygiene control before CIRT and during follow up adopted in CIRT facilities around the world, and at our center. Acute mucositis developed during the CIRT course (also significantly correlated with ORN in our series) together with the high radiation dose to the maxilla alveolar bone portion, might lead to superficial and then deep periodontal disease, gingival recession with increase susceptibility to infection with progressive bone injury leading to ORN ( 24 ). The elimination of odontostomatological risk factors (traumatic, inflammatory, and infectious events) and not, before the start of CIRT and during follow up, is of considerable importance for the outcome of the treatments and the quality of life of the patients.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…These data, together with data with conventional photon RT on the impact of dental infection on ORN incidence ( 28 ), confirm the benefit of pre-CIRT prophylactic dental avulsion and oral hygiene control before CIRT and during follow up adopted in CIRT facilities around the world, and at our center. Acute mucositis developed during the CIRT course (also significantly correlated with ORN in our series) together with the high radiation dose to the maxilla alveolar bone portion, might lead to superficial and then deep periodontal disease, gingival recession with increase susceptibility to infection with progressive bone injury leading to ORN ( 24 ). The elimination of odontostomatological risk factors (traumatic, inflammatory, and infectious events) and not, before the start of CIRT and during follow up, is of considerable importance for the outcome of the treatments and the quality of life of the patients.…”
Section: Discussionmentioning
confidence: 61%
“…With a similar study design, in Sasahara et al the V50 MKM was found to be a risk factor at multivariate analysis, along with the presence of teeth in the PTV, in a series with different radioresistant tumors including ACC treated with CIRT at a prescription dose of 57.6 Gy (RBE) ( 13 ). As pointed out in Musha et al, the adjustment for the RBE model is necessary in CIRT facilities outside Japan ( 24 ), when investigating for dosimetric factors predisposing to toxicity such as ORN. As part of our investigation, here we wanted to translate the V50 MKM , significant factor for ORN reported for the Japanese series ( 13 ), into the corresponding V D extrapolated from our LEM optimized plans recalculated with the MKM Japanese radiobiological model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI is the best imaging modality to evaluate soft tissues in the case of ORNJ owing to the absence of radiation exposure in MRI exams, despite the recommendation that CBCT evaluation of lesion details be performed (37,117). Musha et al stated that stage 1 of ORNJ had a median of 9 months (range, 1-44), for changes be seen on MRI, and that MRI could detect cases without symptoms such as pain (118). The superb ability of diagnosing ORNJ with MRI in the early stages without symptoms would be a huge benefit for its management.…”
Section: Discussionmentioning
confidence: 99%
“…Consiste na isquemia do osso após intensas radiações e caracteriza-se pela sintomatologia dolorosa, necrose, infecção crônica e, em alguns casos, deformidades permanentes. Em pacientes com lesões avançadas, a ressecção da mandíbula torna-se necessária (Musha et al, 2021).…”
Section: Osteorradionecroseunclassified